DGKζ exerts greater control than DGKα over CD8+ T cell activity and tumor inhibition. (1st January 2021) - Gu, Junchen; Wang, Cindy; Cao, Carolyn; Huang, Jinwen; Holzhauer, Sandra; Desilva, Heshani; Wesley, Erin M.; Evans, Douglas B.; Benci, Joseph; Wichroski, Michael; Wee, Susan; Riese, Matthew J.
ABSTRACT: Two isoforms of diacylglycerol kinases (DGKs), DGKα and DGKζ, are primarily responsible for terminating DAG-mediated activation of Ras and PKCθ pathways in T cells. A direct comparison of tumor growth between mice lacking each isoform has not been undertaken. We evaluated the growth of three syngeneic tumor cell lines in mice lacking either DGKα or DGKζ in the presence or absence of treatment with anti-PD1 and determined that (i) mice deficient in DGKζ conferred enhanced control of tumor relative to mice deficient in DGKα and (ii) deficiency of DGKζ acted additively with anti-PD1 in tumor control. Consistent with this finding, functional and RNA-sequencing analyses revealed greater changes in stimulated DGKζ-deficient T cells compared with DGKα-deficient T cells, which were enhanced relative to wildtype T cells. DGKζ also imparted greater regulation than DGKα in human T cells. Together, these data support targeting the ζ isoform of DGKs to therapeutically enhance T cell anti-tumor activity.